1999
DOI: 10.1002/(sici)1097-0215(19990219)84:1<10::aid-ijc3>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Levels of vascular endothelial growth factor, hepatocyte growth factor/scatter factor and basic fibroblast growth factor in human gliomas and their relation to angiogenesis

Abstract: Angiogenesis is a possible target in the treatment of human gliomas. To evaluate the role of 3 growth factors, vascular endothelial growth factor (VEGF), hepatocyte growth factor/scatter factor (HGF/SF) and basic fibroblast growth factor (bFGF), in the angiogenic cascade, we determined their levels in extracts of 71 gliomas by enzyme‐linked immunosorbent assay (ELISA). The levels of bFGF were only marginally different between gliomas of World Health Organization (WHO) grade II (low grade) and grades III and IV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
118
1
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 262 publications
(125 citation statements)
references
References 23 publications
2
118
1
4
Order By: Relevance
“…Discussion c-Met and its ligand SF/HGF are strongly upregulated in malignant gliomas compared with normal brain and also with low grade gliomas. 6,7,33 However, little is known about the mechanisms how this upregulation occurs. Although studies by one group suggested that c-met was amplified in a subset of glioblastomas, 34 this was not confirmed by others.…”
Section: Hypoxia Synergizes With Sf/hgf In Inducing Glioma Cell Migramentioning
confidence: 99%
“…Discussion c-Met and its ligand SF/HGF are strongly upregulated in malignant gliomas compared with normal brain and also with low grade gliomas. 6,7,33 However, little is known about the mechanisms how this upregulation occurs. Although studies by one group suggested that c-met was amplified in a subset of glioblastomas, 34 this was not confirmed by others.…”
Section: Hypoxia Synergizes With Sf/hgf In Inducing Glioma Cell Migramentioning
confidence: 99%
“…Multiple tumor types have been defined as expressing potent angiogenic cytokines such as basic fibroblast growth factor (FGF-2), vascular endothelial growth factor (VEGF), interleukin-8 (IL-8), and angiogenin, among others (Abdulrauf et al, 1998;Dosquet et al, 1997;Kumar et al, 1998;Mattern et al, 1997;Mise et al, 1996;Potgens et al, 1995;Schmidt et al, 1999;Volm et al, 1999). Both FGF-2 and VEGF expression has been strongly correlated with vascular density, metastatic potential, and poor survival in human colon, breast, prostate, and melanoma (Abdulrauf et al, 1998;Dosquet et al, 1997;Mattern et al, 1997;Okita et al, 1998;Schmidt et al, 1999;Ueki et al, 1995;Volm et al, 1999;Xerri et al, 1996).…”
mentioning
confidence: 99%
“…Both FGF-2 and VEGF expression has been strongly correlated with vascular density, metastatic potential, and poor survival in human colon, breast, prostate, and melanoma (Abdulrauf et al, 1998;Dosquet et al, 1997;Mattern et al, 1997;Okita et al, 1998;Schmidt et al, 1999;Ueki et al, 1995;Volm et al, 1999;Xerri et al, 1996). FGF-2, which is not secreted through vesicular pathways, can be exported from cells with unique extrusion pathways or large amounts can be released on cell death (Florkiewicz et al, 1995(Florkiewicz et al, , 1998Kiefer et al, 1993).…”
mentioning
confidence: 99%
“…To trigger this process, tumor cells release a number of angiogenic growth factors such as vascular endothelial growth factor (VEGF), fibroblast growth factor basic (bFGF) and scatter factors. [6][7][8] Many angiogenic proteins, which are potential targets for pharmacological inhibitory strategies, depend on heparan sulfate for their biological functions. 9,10 Heparan sulfate is found on the cell surface and in the extracellular matrix where it plays a central role in growth factor regulation.…”
Section: Uiccmentioning
confidence: 99%